Pengaruh Financial Knowledge, Financial Awareness, Financial Experience, Pendapatan Dan Financial Technology Terhadap Personal Finansial planning Generasi Z Di Kota Metro - Sari, Sri Puspita; Zanaria, Yulita; Darmayanti, Elmira Febri (Universitas Muhammadiyah Metro, 2023)
This study aimed to analyze the effect of Financial Knowledge, Financial Awareness, Financial Experience, Income, and Financial Technology on Personal Financial Planning of Generation Z in Metro City. The population in this study were generation Z in Metro city which were in the productive age category, namely 15-28 years old. The sampling technique in this study used purposive sampling technique using the Slovin formula so that a sample of 100 respondents were obtained. The data were analyzed using multiple linear regression analysis methods. The results showed that Financial Knowledge (X1), Financial Awareness (X2), Income (X4), and Financial Technology (X5) affected the Personal Financial Planning of generation Z in Metro City. While Financial Experience (X3) had no effect on Personal Financial Planning generation Z in Metro city.